(untitled) (Circe de clásicos y modernos, 2018)
In this article we attempt to consider the subject of vita activa and vita contemplativa in the work of Poggio Bracciolini (1380-1459), concentrating there-fore mainly in his dialogue De infelicitate principum. Our hypothesis is that, in this text, there’s a confrontation, without reaching a final thesis, between two different concepts of happiness (one as ‘prevalence’, the other as ‘tranquility of the soul’). On the other hand, this academic and Ciceronian lack of a definitive response leaves open, in the dialogue, a general questioning about the human being and his culture in those years of the Italian Quattrocento.